Public attitudes towards preventive genomics and personal interest in genetic testing to prevent disease: a survey study - Eric Vermeulen; Lidewij Henneman; Carla van El; Martina C. Cornel (2013)
Background: Genetic testing and family history assessment can be used as an aid in the prevention of common chronic diseases. The aim of this study was to determine public attitudes and interests towards offering genetic testing and family history-based risk assessment for common chronic disease prevention. Methods: Cross-sectional questionnaire survey of a consumer panel representative for the Dutch population. The questionnaire was sent to 1399 panel members, aged ≥18 years. Results: The response was 70% (978/1399). About half of the respondents expressed an interest in genetic testing to prevent specific diseases (cancer, cardiovascular disease, diabetes or dementia), with lower-educated respondents showing more interest than higher-educated respondents. Few respondents (24%) agreed that people should be preventively tested for all kinds of diseases. According to the respondents, genetic testing should be performed in the hospital (66%) and be directed to curable (57%) or preventable diseases (69%). Half of the respondents believed that family history assessment could help prevent disease, but only 21% thought it should be offered to everyone, as this could cause people to be worried. A minority (12%) reported that their family history had been assessed, whereas 59% did not have it assessed and did not think this would be necessary. Respondents have differentiated interests in preventive genomics, which varies depending on sex, age and level of education. Conclusions: Members of the public are interested in genetic testing for preventable and curable diseases, but they are ambivalent about family history risk assessment to prevent disease.